A Cognitive Study of Numerical Component Phraseological Units (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the mental processes behind phraseological units featuring numbers, concentrating on the role of numbers as both conceptually and culturally important parts of figurative language. Utilizing a cognitive linguistics framework, the research investigates how conceptual metaphors, image schemas, and cultural models influence the meaning and figurative significance of numerical idioms in both English and Uzbek. Through both comparative and descriptive methods, the study illustrates that numerical phraseological units are influenced by common cognitive frameworks like quantification, categorization, and scaling, while also showing specific cultural meanings related to numbers such as three, seven, nine, and forty. The results indicate that numerical idioms are not random language forms but constructions rooted in cognition that reflect shared experiences, historical customs, and cultural perspectives. By exploring the cognitive and cultural aspects of numerical phraseology, this research enhances understanding of the connection between language, thought, and culture, providing insights into how numerical ideas influence figurative meanings in various languages.